Cholic Acid Protects In Vitro Neurovascular Units against Oxygen and Glucose Deprivation-Induced Injury through the BDNF-TrkB Signaling Pathway. (12th October 2020) - Li, Changxiang; Wang, Xueqian; Yan, Juntang; Cheng, Fafeng; Ma, Xiaona; Chen, Congai; Wang, Wei; Wang, Qingguo
Abstract : Ischemic stroke (IS) can disrupt various types of brain cells in the neurovascular unit (NVU) at both the structural and functional levels. Therefore, NVU is considered to be a more comprehensive target for the treatment of IS. It is necessary to develop drugs which targeted multiple mechanisms and cell types on NVU against IS. As a component of bile acid, cholic acid has been reported to be able to diffuse across phospholipid bilayers and further cross the blood-brain barrier (BBB). However, the effects exerted by cholic acid (CA) on the NVU after stroke remain unclear. Based on our previous research, we established and further supplemented the characteristics of the functional in vitro NVU model and its oxygen-glucose deprivation and reoxygenation (OGD/R) model. Then, we investigated the effect of CA on the maintenance of the in vitro NVU after OGD/R and further discussed the specific molecular targets that CA played a role in. For the first time, we found that CA significantly maintained BBB integrity, downregulated apoptosis, and mitigated oxidative stress and inflammation damage after OGD/R. Meanwhile, CA obviously increased the levels of brain-derived neurotrophic factor (BDNF), which were mainly secreted from astrocytes, in the coculture system after OGD/R. The results demonstrated that CA significantly increased the expression of TrkB, PI3K/Akt, MAPK/Erk, and CREB in neurons. These positive effects on the downstream proteins of BDNF were suppressed by treatment with ANA12 which is an inhibitor of TrkB. In conclusion, the present study demonstrates that CA exerted multiple protective effects on the NVU, mediated by increasing the release of BDNF and further stimulating the BDNF-TrkB-PI3K/Akt and BDNF-TrkB-MAPK/Erk signaling pathways in the context of OGD/R-induced injury. These findings indicate that CA possesses the effect of antagonizing multiple mechanisms of IS and protecting multiple cell types in NVU and may be useful as a treatment for IS.